Transfer of Lipophilic Drugs from Nanoemulsions into Lipid-Containing Alginate Microspheres - Sabrina Knoke; Heike Bunjes (MDPI AG, 2021)
Knowledge about the release behavior and drug retention properties of colloidal carriers is of essential importance for quality control as well as to predict in vivo performance. When conducting release studies from such systems, the release media should preferentially contain lipophilic acceptor components in order to mimic physiological conditions. In this study, transfer from a trimyristin nanoemulsion into lipid-containing hydrogel beads was investigated for fenofibrate, cannabidiol, retinyl acetate, orlistat, and lumefantrine. To generate the acceptor system, a trimyristin nanoemulsion was incorporated into Ca-alginate microspheres (mean diameter ~40 µm) with a spraying method. Using this approach, the advantages of small lipophilic acceptor particles with a large interfacial area were combined with a single separation process from the donor via a filtration step. The method was applicable to distinguish between fast (fenofibrate) and slow drug transfer (lumefantrine) with good time resolution. Lipophilicity, estimated according to the calculated logP value of the respective drug, was a major factor influencing the transfer performance: the higher the logP value, the slower the transfer. This experimental setup is a promising technique to investigate the release of poorly water-soluble drugs from various types of nanocarriers under closer to physiological conditions than with many other methods currently applied.